Daytime Sleepiness in Patients Diagnosed with Sarcoidosis Compared with the General Population - Andreas Hinz; Kristina Geue; Markus Zenger; Hubert Wirtz; Andrea Bosse-Henck (Canadian Respiratory Journal)
Background. The aim of this study was to analyze daytime sleepiness in a sample of patients diagnosed with sarcoidosis. Methods. A sample of 1197 German sarcoidosis patients was examined with the Epworth Sleepiness Scale (ESS), the Fatigue Assessment Scale, the Hospital Anxiety and Depression Scale, the Pittsburgh Sleep Quality Index, and the Short-Form Health Survey (SF-8). The patients’ ESS mean scores were compared with those obtained from a large general population sample. Results. Exactly 50% of the patients reached the criterion (ESS > 10) for excessive daytime sleepiness, compared with only 22.1% in the general population. The effect size for the mean score difference between both samples was d=0.62. The number of affected organs and the number of concomitant diseases proved to be significant independent predictors of daytime sleepiness. Sleepiness was associated with fatigue (r=0.45), anxiety (r=0.23), depression (r=0.28), sleep problems (r=0.23), and detriments in physical (r=−0.29) and mental (r=−0.28) quality of life. Conclusions. The issue of excessive daytime sleepiness should be considered in the management of sarcoidosis.